Karakteristik Petani Sagu dalam Pengembangan Agroindustri Sagu Rakyat di Kabupaten Kepulauan Meranti provinsi Riau - Vermila, Chezy WM; Syahni, Rahmat; Khairati, Rusda; Mutiara, Vonny Indah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to: (1) determine the characteristics of sago farmers in Meranti Islands Regency; and (2) knowing the role of farmers in developing the people's sago agro-industry. This research uses a survey method with the help of a questionnaire. This research is further research with the survey method used. The number of samples used in this research is the number of research parameters multiplied by the indicators. The number of indicators in the main research was 5 x 20 so that 100 samples were obtained. The data analysis used is descriptive analysis. The results of the research show that the characteristics of Sago Farmers as seen from age, education, number of family dependents, land area and experience in sago farming are a reflection of the farmer's ability to develop the people's sago agroindustry. The local value of people's processed sago products is the ability possessed by farmers because of their ability to process sago into various products, as well as the existing decision-making mechanism for sago farmers still using a discussion system with traditional leaders (ninik mamak) community leaders, because traditional culture is still implemented with very good.